2000
DOI: 10.1541/ieejias.120.372
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Control of a Gait of Snake Robot

Abstract: In this paper, we develop a model of a snake-like robot consisting of n rigid links and propose several control strategies to achieve smooth undulative locomotion and position control. The model is based on nonholonomic velocity conditions that arise from non-slipping assumption about the wheels. Singular postures of the robot are analyzed and they are taken in account while deriving the control law. The control strategies are based on Lyapunov method and on constraining the trace of the snake's head into some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 6 publications
0
48
0
Order By: Relevance
“…Furthermore, in [10] it is shown that the fundamental properties of the simplified model such as stabilizability and controllability, are essentially the same as the more complex models presented in several previous works, see e.g. [4,5,12].…”
Section: Modellingmentioning
confidence: 80%
See 2 more Smart Citations
“…Furthermore, in [10] it is shown that the fundamental properties of the simplified model such as stabilizability and controllability, are essentially the same as the more complex models presented in several previous works, see e.g. [4,5,12].…”
Section: Modellingmentioning
confidence: 80%
“…Kinematic and dynamic models of snake robots are previously derived in several works (see e.g., [4,5,10,12]). The snake robot is modelled using a series of prismatic joints which move the robot forward by translational displacements.…”
Section: B a Simplified Model Of The Snake Robotmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of previous control approaches are based on specifying directly the motion of each individual joint angle of the snake robot, which means that the overall body shape motion is controlled implicitly through the joint angles (see e.g. [3]- [5]). This approach works well during motion on flat surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…These constraints allow the control input to be specified directly in terms of the desired propulsion of the snake robot, which is employed in e.g. [2][3][4][5] for computed torque control of the position and heading of wheeled snake robots. Path following control of wheel-less (i.e.…”
Section: Introductionmentioning
confidence: 99%